A survey and improvement of quality at Dataran Setar Sdn Bhd - Seow, Wenjia (2016)
Define, Measure, Analyse, Improve and Control (DMAIC) is one of the problems solving methodology of Six Sigma that used to improve quality. This research presents a case study of surveying quality problems in small scale industry by using Six Sigma approach within a production department. The goals of this research are to improve the quality of services to meet customer demand using DMAIC methodology. This research had shown how the root causes being identified and how the quality of service is being improved and meet customer satisfaction. The defect of quality of service detected is the garment could not complete on time. The analysis from adopting DMAIC indicated that number of workers and machines’ capability influenced the production of the garment. In particular, some calculation using formula has been done to calculate the number of workers needed and change the type of the machines. Six Sigma implementation resulted significant increases in number of workers to produce improvements in productivity. The number of workers has been increase from 15 to 24 workers. As a result, when the productivity of garment increases, customer could get their products on time.